Exploring Illocutionary Speech Acts in Yasmin Mogahed's Dakwah Videos: A Pragmatic Study - Dipta, Dinar; Karim, Norhayati binti Haji Abd; Sholeh, Amira Said (Universitas Islam Ahmad Dahlan (UIAD), 2024)
Illocutionary speech acts refer to intentionally producing an utterance to achieve a specific purpose. This study aims to determine the types and functions of illocutionary speech acts in Yasmin Mogahed's Islamic lessons. This was a qualitative study to perform a content analysis. The data were from Yasmin Mogahed’s utterances through her speech on her YouTube account. Those utterances were selected using the types and functions of the speech act’s checklist. Only the utterances that contain illocutionary speech acts were used as the data. Therefore, these utterances were collected through documentation and a rater of linguistics to check the data accuracy. Later, the data were analyzed through reduction, display, and conclusion drawing. It was found that the types of illocutionary speech acts in Yasmin Mogahed’s speech included: (1) Assertive that consists of stating, concluding, and reporting; (2) Directives that consist of asking, requesting, and ordering; (3) Commissive that consists of promising and planning; and (4) Expressive that includes revealing the psychological state. The type of illocutionary act that appeared the most was assertive with an appearance frequency of 650 utterances, followed by directive of 202 utterances, expressive of 12 utterances, and commissive of 10 utterances. Meanwhile, the functions of the illocutionary act performed by Yasmin Mogahed were: (1) Competitive that includes begging, asking, and ordering; (2) Convivial that includes thanking, congratulating, and greeting; and (3) Collaborative that includes asserting, announcing, and instructing. The functions of illocutionary speech acts in Yasmin Mogahed’s video were revealed as collaborative of 659 utterances, competitive of 193 utterances, and convivial of 22 utterances. It indicates that during her speech, Yasmin Mogahed performs assertive type and collaborative functions since both especially aim to state only the truth hence, she frequently expresses what is considered correct according to Islamic lesson. Highlighting the findings, learning speech acts can be used to minimize communication misunderstandings hereafter.